Interactions of carbon nanotubes and lipid bilayers - Rzepala, W (2013)
The biological membrane, which is composed of a lipid bilayer embedded with numerous proteins, defines the cell boundary, separating the cell interior from the external environment. It serves as a gatekeeper and entry point for various molecular and ionic species. This thesis describes experimental and simulation studies of the interactions of carbon nanotubes (CNTs) with model membranes (lipid bilayers). The unique properties of CNTs make them ideal candidates for many nanotechnological applications. They can, however, pose a potential risk as toxins. While research into the positive benefits of CNTs continues, very little is known about their basic interactions with cellular components. It is particularly important to understand the interaction of CNTs with biological membranes, which form the primary physical barrier surrounding a cell. Coarse grained molecular dynamics (MD) simulations and atomic force microscopy (AFM) have been used to study the interactions of CNTs and lipid bilayers. They are investigated in a controlled manner using MD simulations, while AFM has allowed the controlled approach-to-contact and insertion of CNTs into bilayers. A number of effects are reported, including lipid creep along the CNT and bilayer thickening upon contact. The robustness of this response is established using different force fields and lipid species. The experimental results show an unusual reaction to mechanical indentation, and are further backed by MD simulations. The lipid bilayer response to multiple CNTs is studied and the effects of CNTs on bilayer conformation and lipid diffusion are reported. CNT internalisation from the solvent is observed in the simulations. Indeed, many of the observed phenomena are reminiscent of those known from the field of membrane protein. This project focuses on understanding the basic molecular interactions of CNTs with lipid bilayers and addresses the gap between experimental and computational work.